New genera and species of Selenomorphini (Hemiptera: Cicadellidae: Iassinae), including redescription of Scaroidana Osborn, Pachyopsis Uhler and updated key to genera and species - Domahovski, Alexandre Cruz (Zootaxa, 2019)
Selenomorphini is a small tribe previously comprising four genera and 21 species, with distribution in the New World and New Caledonia. Herein are described three new species of Pachyopsis Uhler from Brazil: P. fasciatus sp. nov., P. nigrifacis sp. nov., and P. pallidus sp. nov. Two new Brazilian monotypic genera, Parapachyopsis gen. nov. and Uhleriana gen. nov. are proposed, based on P. tenebris sp. nov. and U. tornatucephala sp. nov., and an updated key to genera of Selenomorphini is provided. Pachyopsis and Scaroidana are reviewed and the detailed morphology is redescribed, including characters not previously observed and the first illustrations of the female genitalia. The type-species Scaroidana flavida Osborn is redescribed and a key to males of Pachyopsis is provided. Additionally new State records for Brazil are reported for Pachyopsis vicosensis Coelho, Scaroidana flulvula Osborn and Scaroidana flavida Osborn. Detailed comparative notes between the new genera, Pachyopsis and Scaroidana are given.